Mollusc diversity associated with the non-indigenous macroalga Asparagopsis armata Harvey, 1855 along the Atlantic coast of the Iberian Peninsula. (May 2018) - Rubal, Marcos; Costa-Garcia, Ricardo; Besteiro, Celia; Sousa-Pinto, Isabel; Veiga, Puri
Abstract: The aims of this study were to explore mollusc assemblages associated with the non-indigenous macroalga Asparagopsis armata, to compare them with those on other macroalgae at the study region and to explore potential differences on mollusc assemblages between two regions in the Atlantic coast of the Iberian Peninsula, where A. armata is present. To achieve this, at each region, four intertidal shores were sampled. Twenty-nine mollusc species were reported and thus, A. armata harboured similar or higher diversity than other annual macroalgae in this area. When compared with perennial macroalgae, results depend on the species and studied area. Moreover, significant differences in structure of mollusc assemblages between the two studied regions were found. However, these were due to differences in the relative abundance of species rather than the presence of exclusive species at each region. Graphical abstract: Highlights: Mollusc assemblages associated with the non-indigenous macroalga Asparagopsis armata . A. armata along Iberian Peninsula Atlantic coast supports a diverse mollusc assemblage. Mollusc assemblage structure between north and south regions showed differences. A. armata did not show differences on morphological complexity between regions.